SANTRIPRENEURSHIP AND LOCAL WISDOM: ECONOMIC CREATIVE OF PESANTREN MIFTAHUL ULUM - Hannan, Abd (IAIN Surakarta, 2019)
Madura is well-known as an island which has been identical to the values of religion. One of the values is the important role of religious institutions, such as pesantren. The role of pesantren as a traditional Islamic institution is not limited to religious areas only, but to other social aspects only, including in economic development. This study examines the economic development of pesantren through analyzing santripreneur based on local wisdom in Pamekasan, Madura, East Java, Indonesia. This study outlines descriptive-narrative explanations regarding the value of Madurese local wisdom, and creative economic santripreneur activities in the pesantren, such as batik crafts, pesantren supermarket, and sharia-based pesantren (ikhtisab) as an economic development strategy in the pesantren of Miftahul Ulum, Pamekasan. Moreover, it offers the idea of pesantren economic development in Madura, especially in the context of strengthening the economic independency and sustainability. Keywords: Madura, santri, entrepreneurship, local wisdom